The Fe-Gd Phase Diagram - Atiq, S.; West, D. R. F.; Rawlings, R D D (Biological Sciences - PJSIR, 2005)
The results of an experimental investigation of the iron-rich portion of the Fe-Gd system have confirmed previous studies showing that four incongruently melting intermetallic compounds exist, namely, Fe17Gd2,Fe23Gd6,Fe3Gd and Fe2Gd. The investigation also provided information about the crystal structures and ranges of stoichiometry of these intermetallic compounds.